Corrosion resistant adhesive sol-gel
By applying a sol-gel coating containing corrosion inhibitors and surfactants on a metal substrate, and adding an organic primer coating with multiple metal particles, the corrosion resistance of the sol-gel film in the prior art is solved by applying a sol-gel coating containing corrosion inhibitors and surfactants on a metal substrate, and adding an organic primer coating with multiple metal particles. The problem of insufficient performance achieves high adhesion and good corrosion resistance.
Patent Information
- Application Number
- CN202380051691.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-06
- Filing Date
- 2023-05-05
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art has challenges in improving the adhesion and corrosion resistance of metal substrates, especially in the absence of chromate, the corrosion resistance of the sol-gel film is insufficient, resulting in corrosion on the metal surface.
A sol-gel coating containing corrosion inhibitors, surfactants and epoxy-containing organosilanes, metal alkoxides and acid reaction products is applied thereto, and an organic primer coating with multiple metal particles is applied thereto. Enhance adhesion and corrosion resistance.
It achieves the improvement of the adhesion and corrosion resistance of the metal substrate without the use of chromate, significantly reduces corrosion on the metal surface, and meets the corrosion resistance needs of aerospace applications.
Smart Images

Figure CN119487133A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application claims the benefit of priority to U.S. Application No. 63 / 339,276, filed May 6, 2022, the entire contents of which are incorporated herein by reference. Technical Field
[0003] Aspects of the present disclosure generally relate to corrosion resistant sol-gel films for aerospace applications. Background Art
[0004] Metals used in the manufacture of aircraft, spacecraft, and other machinery, such as steel, aluminum, aluminum alloys, and galvanized metals, are susceptible to corrosion. Chromates, such as zinc salts of hexavalent chromium, have been used as corrosion inhibitors in corrosion inhibiting coatings such as paints, sealants, and primers. However, chromates and other corrosion inhibitors generally have poor adhesion to metal substrates. In addition, there is regulatory pressure to eliminate the use of hexavalent chromium and other chromates in conversion coatings, primers, and manufacturing processes.
[0005] Traditionally, adhesive sol-gel films are placed at the interface between a metal substrate and a corrosion inhibitor to promote adhesion. However, adhesive sol-gels do not have corrosion resistance properties by themselves. Therefore, over time, pores that retain moisture are formed in the sol-gel, thereby promoting corrosion of the metal surface. It is desirable to attempt to incorporate chromate-deficient corrosion inhibitors and other primers (such as aluminum primers) to improve adhesion to the metal substrate or primer placed on the sol-gel while maintaining corrosion protection.
[0006]
[0006] Therefore, there is a need in the art for a sol-gel having corrosion inhibiting capabilities that is able to maintain adequate adhesion to a metal substrate when a primer coating is applied. Summary of the invention
[0007] The present disclosure relates to a coated substrate having a metal substrate and a sol-gel coating disposed on the metal substrate. The sol-gel includes a corrosion inhibitor, a surfactant, and a reaction product of an epoxy-containing organosilane, a metal alkoxide, and an acid. The coated substrate includes an organic primer coating having an organic primer having a plurality of metal particles.
[0008] The present disclosure also relates to a method of preparing a coated substrate. The method includes applying a sol-gel coating to a metal substrate to form a sol-gel coating, the sol-gel coating including a corrosion inhibitor. The method includes applying a primer coating to the sol-gel coating to form a primer coating, the primer coating including a metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In order to understand the above features of the present disclosure in detail, the present disclosure briefly summarized above may be described in more detail with reference to some aspects shown in the accompanying drawings. However, it should be noted that the accompanying drawings only illustrate typical aspects of the present disclosure and are therefore not to be considered as limiting the scope thereof, as the present disclosure may admit of other equally effective aspects.
[0010] Figure 1 is a side view of a corrosion inhibiting sol-gel disposed on a substrate in accordance with various aspects of the present disclosure.
[0011] Figure 2 is a schematic diagram of a method of preparing a coated substrate according to various aspects of the present disclosure.
[0012] Figure 3 is an illustrative potentiodynamic scan of a metal surface of a corrosion resistant sol-gel according to various aspects of the present disclosure.
[0013] Figure 4 is an illustrative OPR current graph of a corrosion resistant sol-gel according to various aspects of the present disclosure.
[0014] Figure 5 is an illustrative current-voltage graph of a corrosion-resistant sol-gel on an electrode surface according to various aspects of the present disclosure.
[0015] Fig. 6A and 6B is a SEM image depiction of a corrosion resistant sol-gel according to various aspects of the present disclosure. Fig. 6A is a SEM image of a thin corrosion-resistant sol-gel. Figure 6B is a SEM image of a thick corrosion resistant sol-gel.
[0016] Figure 7 is an illustrative corrosion-resistant sol-gel thickness graph of a corrosion-resistant sol-gel according to various aspects of the present disclosure.
[0017] Figure 8 is an illustrative corrosion resistant sol-gel coating weight graph of corrosion resistant sol-gels according to various aspects of the present disclosure.
[0018] Fig. 9 is an illustrative absorption spectrum of a corrosion resistant sol-gel according to various aspects of the present disclosure.
[0019] Fig.10 is an illustrative current-voltage graph of a corrosion resistant sol-gel according to various aspects of the present disclosure.
[0020] Fig.11 Depicted is a corrosion resistant sol-gel on bare 2024-T3 after 336 h according to various aspects of the present disclosure.
[0021] Fig.12 is an illustrative impedance spectrum of a corrosion resistant sol-gel according to various aspects of the present disclosure.
[0022] Figures 13A-13F are depictions of substrates coated with corrosion resistant sol-gels according to various aspects of the present disclosure and comparators after 2000 h of ASTM B117 exposure. Fig.13A is the first substrate coated with the comparative after 2000h of ASTM B117 exposure. Fig. 13B It is a first substrate coated with a first corrosion resistant sol-gel after 2000h exposure according to ASTM B117. Fig. 13C It is a first substrate coated with a second corrosion resistant sol-gel after 2000h exposure according to ASTM B117. Fig.13D is a second substrate coated with a comparator after 2000 h of ASTM B117 exposure. Fig.13E The second substrate is coated with the first corrosion resistant sol-gel after 2000 h of ASTM B117 exposure. Fig.13E It is a second substrate coated with a second corrosion resistant sol-gel after 2000 h of ASTM B117 exposure.
[0023] Figures 14A-14C are depictions of bare 7075-T6 panels coated with corrosion resistant sol-gels according to various aspects of the present disclosure and comparators after 9 months of outdoor exposure. Fig.14A is bare 7075-T6 coated with comparator. Fig. 14B is bare 7075-T6 coated with the first corrosion resistant sol-gel. Fig. 14C is bare 7075-T6 coated with a second corrosion resistant sol-gel.
[0024] Figures 15A to 15F are depictions of bare Al 7075-T6 panels pretreated with comparative and corrosion resistant sol-gels with various primers according to various aspects of the present disclosure after exposure to a NSS chamber for 2000 h. Fig.15A Depicted is a bare Al 7075-T6 panel pretreated with a comparator having an Al-rich Av-de. Fig. 15B Depicted is a bare Al 7075-T6 panel with Al-rich Av-de pre-treated with a first corrosion resistant sol-gel. Fig. 15C Depicted is a bare Al 7075-T6 panel with Al-rich Av-de pre-treated with a second corrosion resistant sol-gel. Fig.15D Depicted is a bare Al 7075-T6 panel pre-treated with a comparator with Akzo Nobel Aerodur 2118. Fig.15EDepicted is a bare Al 7075-T6 panel with Akzo Nobel Aerodur 2118 pretreated with a first corrosion resistant sol-gel. Fig.15F Depicted is a bare Al 7075-T6 panel with Akzo Nobel Aerodur 2118 pretreated with a second corrosion resistant sol-gel.
[0025] Figures 16A-16D is a depiction of bare 7075-T6 panels with Alodine 1200S as pretreatment, various primers, and PPG 99GY001 polyurethane topcoat after 3000 h of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.16A Depicted is a bare 7075-T6 panel primed with PPG RW 7171-64. Fig. 16B Depicted is a bare 7075-T6 panel primed with an Al-rich Av-dec primer. Fig. 16C A bare 7075-T6 panel primed with Aerodur 2118 is depicted. Fig.16D Depicted is a bare 7075-T6 panel primed with PPG CA7231.
[0026] Figures 17A-17D is a depiction of a bare 7075-T6 panel with Alodine 5900 as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 h of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.17A Depicted is a bare 7075-T6 panel primed with PPG RW 7171-64. Fig. 17B Depicted is a bare 7075-T6 panel primed with an Al-rich Av-dec primer. Fig. 17C A bare 7075-T6 panel primed with Aerodur 2118 is depicted. Fig.20D Depicted is a bare 7075-T6 panel primed with PPGCA7231.
[0027] Figures 18A-18D is a depiction of a bare 7075-T6 panel with SurTec 650V as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 h of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.18A Depicted is a bare 7075-T6 panel primed with PPG RW 7171-64. Fig.18B Depicted is a bare 7075-T6 panel primed with an Al-rich Av-dec primer. Fig.18C A bare 7075-T6 panel primed with Aerodur 2118 is depicted. Fig.18DDepicted is a bare 7075-T6 panel primed with PPGCA7231.
[0028] Figures 19A-19D is a depiction of a bare 7075-T6 panel with the corrosion resistant sol-gel of the present disclosure with DMCT as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 h of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.19A Depicted is a bare 7075-T6 panel primed with PPG RW 7171-64. Fig.19B Depicted is a bare 7075-T6 panel primed with an Al-rich Av-dec primer. Fig.19C A bare 7075-T6 panel primed with Aerodur 2118 is depicted. Fig.19D Depicted is a bare 7075-T6 panel primed with PPG CA7231.
[0029] Figures 20A-20D is a depiction of 7178 panels with Alodine 1200S as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig. 20A Depicted is a bare 7178 panel primed with PPG RW 7171-64. Fig. 20B Depicted is a bare 7178 panel primed with Al-rich Av-dec. Fig. 20C Bare 7178 panel primed with Aerodur 2118 is depicted. Fig.20D Depicted is a bare 7178 panel primed with PPG CA7231.
[0030] Figures 21A-21C is a depiction of 7178 panels with Alodine 5900 as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.21A Depicted is a bare 7178 panel primed with PPG RW 7171-64. Fig.21B Depicted is a bare 7178 panel primed with Al-rich Av-dec. Fig. 21C Bare 7178 panel primed with Aerodur 2118 is depicted.
[0031] Figures 22A-22C is a depiction of 7178 panels with SurTec 650V as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.22ADepicted is a bare 7178 panel primed with PPG RW 7171-64. Fig. 22B Depicted is a bare 7178 panel primed with Al-rich Av-dec. Fig. 22C Bare 7178 panel primed with Aerodur 2118 is depicted.
[0032] Fig.23A and 23B is a depiction of a 7178 panel with the corrosion resistant sol-gel of the present disclosure with DMCT as pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Fig.23A Depicted is a bare 7178 panel primed with PPG RW 7171-64. Fig. 23B Depicted is a bare 7178 panel primed with rich AlAv-dec.
[0033] Fig.24 is a comparative illustration of ranking 7075-T6 test panels that completed 3000 hours of exposure to an NSS chamber using various methods in accordance with various aspects of the present disclosure.
[0034] Fig.25 is a comparative illustration of ranking 7178 test panels that completed 2000 hours of exposure to an NSS chamber using various methods in accordance with various aspects of the present disclosure.
[0035] Fig.26 is a comparative illustration of ranking 7075-T6 test panels exposed in an NSS chamber for 3000 hours and in a cycling chamber for 672 hours according to various aspects of the present disclosure.
[0036] Fig. 27 is a comparative illustration of ranking 7178 test panels exposed in an NSS chamber for 3000 hours and in a cycling chamber for 672 hours according to various aspects of the present disclosure. DETAILED DESCRIPTION
[0037] Various aspects of the present disclosure generally relate to corrosion resistant sol-gels for aerospace applications. The sol-gels of the present disclosure include epoxy-containing organosilanes, metal alkoxides, acid stabilizers (or their reaction products), about 3 wt% to about 15 wt% of a corrosion inhibitor by volume of the total sol-gel coating, and a surfactant. It has been found that the surfactant present in the sol-gel prevents or reduces the porosity and blistering of the sol-gel / primer coating on the metal surface, thereby providing the corrosion inhibition ability of the sol-gel film, because the accumulation of water in the sol-gel can be prevented or reduced. The surfactant can also increase the wettability of the coating on the metal surface, improve the coating adhesion and corrosion performance. In addition, it has been found that the use of an organic primer having a plurality of metal particles (e.g., aluminum, lithium, etc.) placed on the corrosion resistant sol-gel can enhance the corrosion protection of alloys (e.g., aerospace alloys). The sol-gel of the present disclosure has corrosion inhibition ability, and the primer (placed on the sol-gel) can be a chrome-free primer or a chrome-containing primer.
[0038] The method of preparing the coated substrate of the present disclosure includes applying a sol-gel coating to a metal substrate to form a sol-gel coating. The sol-gel coating includes a corrosion inhibitor in an amount of about 3 wt % of the corrosion inhibitor by volume of the sol-gel coating to about 15 wt % by volume of the sol-gel coating.
[0039] Metal substrate
[0040] The metal substrate includes an aircraft metal surface, which may include steel or an alloy with a major component such as aluminum. The metal substrate may include a major component and a minor component, called an intermetallic compound. The intermetallic compound, for example, may contain copper metal that is susceptible to corrosion. The metal substrate may include an aluminum substrate. The metal substrate may include an aluminum substrate with a copper intermetallic compound. As a non-limiting example, the metal substrate may be a 7075-T6 aluminum substrate or a 7178 aluminum substrate.
[0041] Sol-Gel
[0042] The term "sol-gel" is an abbreviation of solution-gelation and refers to a series of reactions in which a soluble metal species (usually a metal alkoxide or metal salt) is hydrolyzed to form a metal hydroxide. The soluble metal species usually contains an organic ligand suitable for corresponding to the resin in the bonding structure. The soluble metal species undergoes isohydrolysis and isocondensation reactions to form heterometallic bonds, such as Si-O-Zr. In the absence of an organic acid, when a metal alkoxide is added to water, a white precipitate such as Zr(OH)2 forms rapidly. Zr(OH)2 is insoluble in water, which hinders the formation of a sol-gel. Acid is added to the metal alkoxide to form a water-based system. Depending on the reaction conditions, the metal polymers can condense into colloidal particles, or they can grow to form a network gel. The ratio of organic to inorganic matter in the polymer matrix is controlled to maximize the performance for a specific application.
[0043] The thickness of the sol-gel is about 50 nm to about 4 μm, for example, about 100 nm to about 2.5 μm, such as about 100 nm, about 200 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 700 nm, about 800 nm, about 900 nm, about 1 μm, about 2 μm, about 2.5 μm, etc. The weight of the sol-gel is about 30 mg / ft 2 About 1000mg / ft 2 , for example about 30 mg / ft 2 About 400mg / ft 2 , or about 250 mg / ft 2 About 1000mg / ft 2 , such as, for example, about 30 mg / ft 2 , about 100mg / ft 2 , about 200mg / ft 2 , about 300mg / ft 2 , about 400mg / ft 2 , about 500mg / ft 2 , about 600mg / ft 2 , about 700mg / ft 2 , about 800mg / ft 2 , about 900mg / ft 2 , about 1000mg / ft 2 wait.
[0044] Organosilanes
[0045] The weight fraction (wt %) of the organosilane in the sol-gel is from about 0.1 wt % to about 20 wt %, such as from about 0.3 wt % to about 15 wt %, such as from about 0.5 wt % to about 10 wt %, such as from about 0.7 wt % to about 5 wt %, such as from about 1 wt % to about 2 wt %, for example about 1 wt %, about 1.5 wt %, about 2 wt %, based on the volume of the total sol-gel coating.
[0046] The organosilane of the present disclosure is represented by formula (I):
[0047]
[0048] in:
[0049] R 2 , R 3 and R 4 Each independently is a straight chain or branched chain C 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and eicosyl;
[0050] R 1 is selected from alkyl, cycloalkyl, ether and aryl. Alkyl includes straight chain or branched C 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. Ether includes polyethylene glycol ether, polypropylene glycol ether, C1-C 20 Alkyl ethers, aryl ethers and cycloalkyl ethers.
[0051] The ether is selected from:
[0052]
[0053]
[0054] wherein n is a positive integer. In at least one aspect, n is a positive integer and the number average molecular weight (Mn) of the ether is from about 300 to about 500, such as from about 375 to about 450, such as from about 400 to about 425.
[0055] The organosilane is a hydroxyorganosilane. Hydroxyorganosilane is substantially unreactive to nucleophiles (e.g., some corrosion inhibitors). The hydroxyorganosilane of the present disclosure is represented by formula (II):
[0056]
[0057] Wherein R is selected from alkyl, cycloalkyl, ether and aryl. Alkyl includes straight chain or branched C 1-20 Alkyl. C 1-20 Alkyl includes methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. Ether includes polyethylene glycol ether, polypropylene glycol ether, C1-C 20 Alkyl ethers, aryl ethers and cycloalkyl ethers.
[0058] The ether is selected from:
[0059]
[0060] wherein n is a positive integer. In at least one aspect, n is a positive integer and the number average molecular weight (Mn) of the ether is from about 300 to about 500, such as from about 375 to about 450, such as from about 400 to about 425.
[0061] The organosilane is represented by Compound 1 or Compound 2:
[0062]
[0063] The organosilane is selected from 3-aminopropyl triethoxysilane, 3-glycidoxy-propyl triethoxysilane, p-aminophenyl trimethoxysilane, p-aminophenyl triethoxysilane, allyl trimethoxysilane, allyl triethoxysilane, n-(2-aminoethyl)-3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-glycidoxypropyl diisopropylethoxysilane, (3-glycidoxypropyl) methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 2-(3,4-epoxycyclohexyl) ethyl trimethoxysilane, 2-(3,4-epoxycyclohexyl) ethyl triethoxysilane, 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-methacryloxypropyl methyl diethoxysilane, 3-methyl Acryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, n-phenylaminopropyltrimethoxysilane, vinylmethyldiethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)ethane, bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]disulfide, bis[3-(trimethoxysilyl)propyl]disulfide, bis[3-(triethoxysilyl)propyl]trisulfide, bis[3-(trimethoxysilyl)propyl]trisulfide, bis[3-(trimethoxysilyl)propyl]tetrasulfide and bis[3-(trimethoxysilyl)propyl]tetrasulfide.
[0064] The organosilanes useful for forming the sol-gels of the present disclosure provide electrophilic silicon and / or epoxide moieties that can react with nucleophiles, such as hydroxyl-containing nucleophiles. The organosilanes of the present disclosure provide sol-gels with reduced porosity and foaming compared to conventional sol-gels.
[0065] Metal alkoxide
[0066] The metal alkoxide that can be used to form the sol-gel of the present disclosure provides the metal atom coordinated in the sol-gel for adhesion and mechanical strength. The metal alkoxide of the present disclosure includes at least one of zirconium alkoxide, titanium alkoxide, hafnium alkoxide, yttrium alkoxide, cerium alkoxide and lanthanum alkoxide. The metal alkoxide can have four alkoxy ligands coordinated with the metal having an oxidation number of +4. The non-limiting examples of metal alkoxide are tetramethoxy zirconium (IV), tetraethoxy zirconium (IV), tetra-n-propoxy zirconium (IV), tetra-isopropoxy zirconium (IV), tetra-n-butoxy zirconium (IV), tetra-iso-butoxy zirconium (IV), tetra-n-pentoxy zirconium (IV), tetra-isopentoxy zirconium (IV), tetra-n-hexoxy zirconium (IV), tetra-isohexoxy zirconium (IV), tetra-n-heptoxy zirconium (IV), tetra-iso-heptoxy zirconium (IV), tetra-n-octoxy zirconium (IV), tetra-iso-octoxy zirconium (IV), tetra-n-nonoxy zirconium (IV), tetra-isononyloxy zirconium (IV), tetra-n-decyloxy zirconium (IV) and tetra-iso-decyloxy zirconium (IV).
[0067] The sol-gel includes a metal alkoxide content, wherein the metal alkoxide content is a metal alkoxide reaction product formed in the sol-gel. The weight fraction (wt%) of the metal alkoxide content by volume in the total sol-gel coating is from about 0.1 wt% to about 10 wt%, such as from about 0.2 wt% to about 5 wt%, such as from about 0.3 wt% to about 3 wt%, such as from about 0.4 wt% to about 2 wt%, such as from about 0.5 wt% to about 1 wt%, for example, about 0.2 wt%, about 0.5 wt%, about 1 wt%.
[0068] Acid stabilizer
[0069] The acid stabilizer used to form the sol-gel of the present disclosure provides stability of the metal alkoxide and corrosion inhibitor of the sol-gel and a reduction in the pH of the sol-gel. The pH of the sol-gel (and the components that form the sol-gel) can be controlled by using an acid stabilizer. Acid stabilizers of the present disclosure include organic acids. Organic acids include acetic acid (such as glacial acetic acid) or citric acid. Acid stabilizers with lower acidity (e.g., pKa greater than the pKa of acetic acid) such as glycols, ethoxyethanol, or H2NCH2CH2OH may also be used.
[0070] The pH of the sol-gel of the present disclosure is from about 2 to about 5, such as from about 3 to about 4. The weight fraction (wt%) of the acid stabilizer by volume in the total sol-gel is from about 0.1 wt% to about 10 wt%, such as from about 0.2 wt% to about 5 wt%, such as from about 0.3 wt% to about 3 wt%, such as from about 0.4 wt% to about 2 wt%, such as from about 0.5 wt% to about 1 wt%, for example, about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%. For example, but not limited to, the wt% of the acid stabilizer in the sol-gel is about 0.5 wt%, and the weight fraction of the metal alkoxide is about 0.6 wt% or greater. As a further non-limiting example, the wt% of the acid stabilizer in the sol-gel is about 0.3 wt%, and the weight fraction of the metal alkoxide is less than 0.6 wt%.
[0071] The ratio of metal alkoxide to acid stabilizer in the sol-gel can be from about 1:1 to about 3:1, such as about 2: 1. The molar ratio of acid stabilizer to metal alkoxide can be from about 1:1 to about 40:1, such as from about 3:1 to about 8:1, such as from about 4:1 to about 6:1, such as from about 4:1 to about 5:1.
[0072] Without being bound by theory, it is believed that these ratios of acid stabilizer not only help stabilize the metal alkoxide for hydrolysis, but also protonate the mercaptan portion of the corrosion inhibitor, thereby reducing or preventing reaction of the corrosion inhibitor with, for example, the metal alkoxide.
[0073] Surfactants
[0074] Without wishing to be bound by theory, surfactants useful in forming the disclosed sol-gels enhance adhesion of the sol-gel to the metal substrate by increasing the surface wettability of the coating on the metal surface. Surfactants can enhance adhesion and are quantified according to wet cross hatch adhesion in accordance with ASTM D3359. For example, but not limitation, a sol-gel with a surfactant can increase wet cross hatch adhesion to a value of 10.
[0075] Without wishing to be bound by theory, the surfactants that can be used to form the sol-gel of the present disclosure provide enhanced adhesion of the sol-gel to the primer. The surfactants of the present disclosure may include surfactants that are capable of undergoing an alkoxylation reaction, wherein addition of an epoxide to the substrate occurs. The surfactant may include one or more alcohol ethoxylates, alcohol propoxylates, ethoxysulfates, polyethoxylated amines, and the like. For example, but not limited to, the surfactant may be ethylene-oxide alcohol, propylene-oxide alcohol, ethylene-oxide-propylene-oxide alcohol, polyethoxylated tallow amine, ethanolamine, diethanolamine, triethanolamine, and the like.
[0076] Corrosion Inhibitors
[0077] Corrosion inhibitors that can be used to form the sol-gel of the present disclosure provide corrosion resistance (to water) to a metal substrate placed adjacent to the sol-gel. The corrosion inhibitors of the present disclosure are compounds having one or more thiol moieties. Aircraft metal surfaces may include steel or alloys having a primary component such as aluminum and a secondary component known as an intermetallic compound. Intermetallic compounds, for example, typically contain copper metal, which is susceptible to corrosion. Without being bound by theory, the interaction of the thiol moiety of the corrosion inhibitor of the present disclosure with the copper-containing intermetallic compound on the metal surface (such as the aluminum alloy surface) prevents corrosion of the metal surface. More specifically, the interaction of the thiol moiety of the corrosion inhibitor of the present disclosure with the intermetallic compound prevents the reduction of the intermetallic compound by slowing down the rate of oxygen reduction and reducing the oxidation of the metal alloy (such as the aluminum alloy).
[0078] The corrosion inhibitors of the present disclosure are organic compounds that include disulfide groups and / or thiol groups (e.g., metal-sulfide bonds). For example, the corrosion inhibitor is not an organic metal corrosion inhibitor. The corrosion inhibitor is of the formula R 1 --S n --X--R 2 Indicates that R 1 is an organic group, n is an integer greater than or equal to 1, X is a sulfur or metal atom, and R 2 is an organic group. 1 and R 2 One or both of the compounds may include additional polysulfide groups and / or thiol groups. In addition, the corrosion inhibitor includes a compound having the formula: 1 --S n --X--R 2 ) q - polymer, wherein R 1is an organic group, n is a positive integer, X is a sulfur or metal atom, R 2 is an organic group, and q is a positive integer. R (of a polymeric or monomeric corrosion inhibitor) 1 and R 2 R is independently selected from H, alkyl, cycloalkyl, aryl, thiol, polysulfide or thione. 1 and R 2 Each of R may be independently substituted with a moiety selected from alkyl, amino, phosphorus-containing, ether, alkoxy, hydroxyl, sulfur-containing, selenium, or tellurium. 1 and R 2 Each has 1 to 24 carbon atoms and / or non-hydrogen atoms. 1 and R 2 Examples of heterocyclic groups include azole, triazole, thiazole, dithiazole and / or thiadiazole.
[0079] The corrosion inhibitor includes a metal in a metal thiolate complex. The corrosion inhibitor may include a metal center and one or more thiol groups (ligands) bound and / or coordinated to the metal center via a metal-sulfide bond. Thiolates are derivatives of thiols in which a metal atom replaces the hydrogen bonded to the sulfur. Thiolates have the general formula MSR 1 , where M is the metal, and R 1 is an organic group. 1 The metal thiolate complex has the general formula M-(SR 1 ) n , wherein n is generally an integer from 2 to 9, and M is a metal atom. The metal is copper, zinc, zirconium, aluminum, iron, cadmium, lead, mercury, silver, platinum, palladium, gold and / or cobalt.
[0080] Corrosion inhibitors include azole compounds. Examples of suitable azole compounds include cyclic compounds with 1 nitrogen atom, such as pyrrole, cyclic compounds with 2 or more nitrogen atoms, such as pyrazole, imidazole, triazole, tetrazole and pentazole, cyclic compounds with 1 nitrogen atom and 1 oxygen atom, such as oxazole and isoxazole, and cyclic compounds with 1 nitrogen atom and 1 sulfur atom, such as thiazole and isothiazole. Non-limiting examples of suitable azole compounds include 2,5-dimercapto-1,3,4-thiadiazole, 1H-benzotriazole, 1H-1,2,3-triazole, 2-amino-5-mercapto-1,3,4-thiadiazole, also known as 5-amino-1,3,4-thiadiazole-2-thiol, 2-amino-1,3,4-thiadiazole. For example, but not limited to, the azole can be 2,5-dimercapto-1,3,4-thiadiazole. The azole may be present in the composition at a concentration of 0.01 g / L to 1 g / L of the sol-gel composition, such as 0.4 g / L of the sol-gel composition.The azole compound may include benzotriazole and / or 2,5-dimercapto-1,3,4-thiadiazole.
[0081] The corrosion inhibitors of the present disclosure include heterocyclic thiols and amines, which can eliminate oxygen reduction. The heterocyclic thiols include thiadiazoles having one or more thiol moieties. Non-limiting examples of thiadiazoles having one or more thiol moieties include 1,3,4-thiadiazole-2,5-dithiol and thiadiazoles represented by formula (III) or formula (IV):
[0082]
[0083] Thiadiazoles of formula (III) are commercially available from Vanderbilt Chemicals, LLC, located in Norwalk, Connecticut, and are referred to as 829. The thiadiazole of formula (IV) is commercially available from WPC Technologies, Inc. TM (located in Oak Creek, Wisconsin) and is called InhibiCor TM 1000.
[0084] The corrosion inhibitors of the present disclosure may be derivatives of 2,5-dimercapto-1,3,4-thiadiazole represented by HS-CN2SC-SH or "DMTD", and selected derivatives of trithiocyanate ("TMT") used as corrosion inhibitors associated with paints. Examples include 2,5-dimercapto-1,3,4-thiadiazole (DMTD), 2,4-dimercapto-s-triazolo[4,3-b]-1,3-4-thiadiazole and trithiocyanate (TMT). Other examples include N-, S- and N,N-, S,S- and N,S-substituted derivatives of DMTD, such as 5-mercapto-3-phenyl-1,3,4-thiadiazolidine-2-thione or bismuth alcohol II (3-phenyl-1,3,4-thiadiazolidine-2,5-dithione) and various S-substituted derivatives of trithiocyanate. Other examples include 5,5'-dithiobis(1,3,4-thiadiazole-2(3H)-thione or (DMTD)2, or (DMTD), polymers of DMTD; 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione; or (TMT)2, dimers and polymers of TMT. Other examples include the general formula M(DMTD) nDMTD salts, wherein n = 1, 2 or 3, M is a metal cation, such as M = Zn (II), Bi (III), Co (II), Ni (II), Cd (II), Pb (II), Ag (I), Sb (III), Sn (II), Fe (II) or Cu (II) (Examples: ZnDMTD, Zn (DMTD) 2, Bi (DMTD) 3); similar salts of TMT, such as ZnTMT in a 1:1 ratio; and equivalent soluble Li (I), Ca (II), Sr (II), Mg (II), La (III), Ce (III), Pr (III) or Zr (IV) salts. Additional examples include the general formula M [(DMTD) n ] m (DMTD) n Salts of wherein n=2 or n>2, M=1, 2 or 3, and M is a metal cation, such as M=Zn(II), Bi(III), Co(II), Ni(II), Cd(II), Pb(II), Ag(I), Sb(III), Sn(II), Fe(II) or Cu(II). Typical examples are: Zn[(DMTD)2], Zn[(DMTD)2]2.
[0085] Additional examples include DMTD, (DMTD) n or an ammonium, arylammonium or alkylammonium salt of 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione or 2,4-dimercapto-s-triazolo[4,3-b]-1,3,4-thiadiazole. Typical examples include: cyclohexylamine:DMTD in ratios of 1:1 and 2:1; dicyclohexylamine:DMTD in ratios of 1:1 and 2:1; aniline:DMTD in ratios of 1:1 and 2:1; similar salts of TMT, such as dicyclohexylamine:TMT in a ratio of 1:1. Other examples include DMTD or (DMTD) formed from polyamines n and polyammonium salts of TMT.
[0086] Additional examples include naturally conductive polyaniline doped with DMTD or (DMTD)2 or 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione and TMT; naturally conductive polypyrrole and / or polythiophene doped with DMTD, (DMTD)2 and 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione and / or TMT.
[0087] Additional examples include micro- or nanocomposites of polyDMTD / polyaniline, polyDMTD / polypyrrole, and polyDMTD / / polythiophene; similar micro- or nanocomposites with TMT; and similar micro- or nanocomposites with 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione; DMTD or salts of DMTD or derivatives of DMTD and TMT as organic components of various pigment-grade inorganic matrices or physical mixtures. Such inorganic matrices may include non-toxic anionic and cationic species having corrosion inhibitor properties, such as: MoO4 - PO4 - 、HPO3 - , polyphosphate, BO2 - 、SiO4 - 、NCN - WO4 - , phosphomolybdate, phosphotungstate, and, respectively, Mg, Ca, Sr, La, Ce, Zn, Fe, Al, Bi.
[0088] Further examples include encapsulated forms of DMTD or salts of DMTD or derivatives of DMTD and TMT, such as inclusion compounds in various polymer matrices, or as cyclodextrin inclusion compounds or microencapsulated forms.
[0089] Pigmentary forms of DMTD include Zn(DMTD)2 and Zn-DMTD (and other organic and inorganic salts of the former) with inorganic products or corrosion inhibitor pigments such as: phosphates, molybdates, borates, silicates, tungstates, phosphotungstates, phosphomolybdates, cyanamides or carbonates of the previously specified cationic species, and oxides. Examples include: zinc phosphate, cerium molybdate, calcium silicate, strontium borate, zinc cyanamide, cerium phosphotungstate, ZnO, CeO2, ZrO2 and amorphous SiO2.
[0090] The corrosion inhibitor is a lithium ion and a counterion, which may include various ions known to form salts with lithium. Non-limiting examples of counterions suitable for forming salts with lithium include carbonates, hydroxides, and silicates (e.g., orthosilicates and metasilicates). For example, the corrosion inhibitor includes a lithium carbonate salt, a lithium hydroxide salt, or a lithium silicate salt (e.g., a lithium orthosilicate salt or a lithium metasilicate salt). The counterion includes various ions known to form salts with other Group IA (or Group 1) metals (e.g., Na, K, Rb, Cs, and / or Fr). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonates, hydroxides, and silicates (e.g., orthosilicates and metasilicates). For example, but not limited to, the corrosion inhibitor includes an alkali metal carbonate, an alkali metal hydroxide salt, and / or an alkali metal silicate (e.g., an alkali metal orthosilicate or an alkali metal metasilicate). For example, some non-limiting examples of suitable salts include carbonates, hydroxides, and silicates (eg, orthosilicates or metasilicates) of sodium, potassium, rubidium, cesium, and rubidium.
[0091] The corrosion inhibitors of the present disclosure include aluminum- and magnesium-rich compounds that can provide cathodic protection of the material. The aluminum-rich corrosion inhibitor includes aluminum or an aluminum alloy, wherein the aluminum or aluminum alloy accounts for more than 50 wt% by volume of the corrosion inhibitor. The magnesium-rich corrosion inhibitor includes magnesium or a magnesium alloy, wherein the magnesium or magnesium alloy accounts for more than 50 wt% by volume of the corrosion inhibitor. The corrosion inhibitors of the present disclosure may include cesium compounds.
[0092] In the total sol-gel, the weight fraction (wt%) of the corrosion inhibitor is from about 1 wt% to about 15 wt% by volume, such as from about 3 wt% to about 15 wt%, such as from about 1 wt% to about 5 wt%, such as from about 5 wt% to about 10 wt%, such as from about 10 wt% to about 15 wt%, such as from about 12 wt% to about 15 wt%, for example about 1 wt%, about 5 wt%, about 10 wt%, about 15 wt%. For example, but not limited to, the wt% of the corrosion inhibitor in the total sol-gel is about 3 wt% to about 15 wt% by volume, and the weight fraction of the metal alkoxide is about 0.6 wt% or more by volume in the total sol-gel. As a further non-limiting example, the wt% of the acid stabilizer in the total sol-gel is about 3 wt% to about 15 wt%, and the weight fraction of the metal alkoxide in the sol-gel is less than 0.6 wt% of the total sol-gel by volume. The corrosion inhibitors incorporated into the sol-gel provide an additional layer of corrosion protection near the metal surface. In addition, this will promote corrosion protection when used over a non-chromated primer coating.
[0093] Primer
[0094] The primer of the present disclosure can be placed on the sol-gel coating to enhance the bonding adhesion of the aluminum surface and the adhesion with the subsequent epoxy primer. The primer of the present disclosure can be composed of a reactive polymer. For example, the primer can be composed of an epoxy resin, such as an amine-cured epoxy resin. The primer of the present disclosure can be composed of a siloxane, such as a polysiloxane. The primer of the present disclosure can include about 0 to about 30 wt % of a corrosion inhibitor by volume in the primer solution.
[0095] The primer of the present disclosure includes an organic primer with multiple metal particles that can prevent corrosion and filiform corrosion caused by fasteners. The metal particles can sacrifice corrosion and inhibit the corrosion of the surface metal by undergoing oxidation before the surface metal. The metal particles can include aluminum ions and counterions, and the counterions can include various ions known to form salts with aluminum. Non-limiting examples of counterions suitable for forming salts with aluminum include carbonate, hydroxide and silicate (e.g., orthosilicate and metasilicate). For example, but not limited to, counterions include aluminum carbonate, aluminum hydroxide or aluminum silicate (e.g., orthosilicate or metasilicate). Counterions can include various ions known to form salts with other Group 13 metals (e.g., B, Ga, In, Tl, Ho and / or Es). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide and silicate (e.g., orthosilicate and metasilicate).
[0096] The metal particles may include magnesium ions and counterions, and the counterions may include various ions known to form salts with magnesium. Non-limiting examples of counterions suitable for forming salts with magnesium include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate). For example, but not limited to, corrosion inhibitors include magnesium carbonate, magnesium hydroxide, or magnesium silicate (e.g., orthosilicate or metasilicate). Counterions may include various ions known to form salts with other Group 2 metals (e.g., Be, Ca, Sr, Ba, and / or Ra). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate).
[0097] The metal particles may include lithium ions and counterions, and the counterions may include various ions known to form salts with lithium. Non-limiting examples of counterions suitable for forming salts with lithium include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate). For example, but not limited to, corrosion inhibitors include lithium carbonate salts, lithium hydroxide salts, or lithium silicate salts (e.g., lithium orthosilicate salts or lithium metasilicate salts). Counterions may include various ions known to form salts with other Group IA (or Group 1) metals (e.g., Na, K, Rb, Cs, and / or Fr). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate).
[0098] The thickness of the primer coating (placed on the sol-gel) is from about 0.3 mil to about 2.5 mils, for example from about 1.0 mil to about 2.0 mils, such as about 0.3 mil, about 0.5 mil, about 1.0 mil, about 1.5 mil, about 2.0 mil, about 2.5 mil, etc.
[0099] Topcoat
[0100] The topcoat of the present disclosure can be placed on the primer coating to form a sol-gel of the present disclosure, which has the corrosion resistance (to water) of the metal substrate placed adjacent to the sol-gel. The topcoat can include an organic topcoat, such as a polymer coating (e.g., an epoxy coating and / or a urethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber reinforced composite material), a laminate, or a mixture thereof. The topcoat includes at least one of a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a lacquer, a polyurethane, a polyester, or a combination thereof. For example, but not limited to, the topcoat is a polyurethane. The polyurethane topcoat prevents water from penetrating the coating, thereby enhancing corrosion protection. The topcoat has a thickness of about 2 mils to about 3 mils, for example, about 2.1 mils to about 2.9 mils, such as about 2 mils, about 2.1 mils, about 2.2 mils, about 2.3 mils, about 2.4 mils, about 2.5 mils, about 2.6 mils, about 2.7 mils, about 2.8 mils, about 2.9 mils, about 3 mils, etc. For example, but not limited to, the topcoat has a thickness of about 2 mils to about 3 mils, and the primer has a thickness of about 0.3 mils to about 2.5 mils.
[0101] Sol-Gel System
[0102] Figure 1 1 is a side view of a corrosion inhibiting sol-gel placed on a substrate. The corrosion inhibiting sol-gel system 100 includes a sol-gel 102 placed on a material substrate 104. The sol-gel 102 has corrosion inhibiting properties that provide corrosion protection for the material substrate 104. The sol-gel 102 promotes adhesion between the metal substrate 104 and a second layer 106. The second layer 106 can be a sealant, adhesive, primer, or coating that can be placed on the sol-gel 102 by, for example, spray drying.
[0103] The material substrate 104 can be any suitable material as described herein and / or can include any suitable structure that benefits from the sol-gel 102 placed thereon. The material substrate 104 can define one or more components (such as structural or mechanical components) of an environmentally exposed device, such as an aircraft, a ship, a spacecraft, a land vehicle, equipment, a civil structure, a fastening component, a wind turbine, and / or other devices susceptible to environmental degradation. The material substrate 104 can be part of a larger structure, such as a vehicle component. The vehicle component is any suitable component of a vehicle, such as a structural component, such as a landing gear, a panel or a joint of an aircraft. Examples of vehicle components include rotor blades, landing gear, an auxiliary power unit, an aircraft nose, a fuel tank, a tail cone, a panel, a coating overlap between two or more panels, a wing to fuselage assembly, a structural aircraft composite material, a fuselage joint, a wing rib to skin joint, and / or other internal components. The material substrate 104 can be made of at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, nickel, iron, iron alloy, steel, titanium, titanium alloy, copper and copper alloy, as well as glass / silicon dioxide and other inorganic or mineral substrates. The material substrate 104 is made of steel. The material substrate 104 can be a 'bare' substrate, with no coating (unplated metal), conversion coating and / or corrosion protection between the material substrate 104 and the sol-gel 102. Additionally or optionally, the material substrate 104 can include surface oxidation and / or hydroxylation. Therefore, the sol-gel 102 can be directly bonded to the material substrate 104 and / or the surface oxide layer on the surface of the material substrate 104. The material is not sensitive to water, but the sol-gel placed on the material can protect other adjacent structures that may be sensitive to water.
[0104] The second layer 106 is disposed on a second surface 110 of the sol-gel 102 opposite the first surface 108 of the sol-gel 102. The thickness of the sol-gel 102 is less than the thickness of the material substrate 104. The thickness of the sol-gel 102 is about 50 nm to about 4 μm, for example, about 100 nm to about 2.5 μm, such as about 100 nm, about 200 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 700 nm, about 800 nm, about 900 nm, about 1 μm, about 2 μm, about 2.5 μm, etc. Thinner coatings may have fewer defects (more likely to be defect-free), while thicker coatings may provide more wear, electrical, and / or thermal protection to the underlying material substrate 104.
[0105] The second layer 106 includes an organic material (e.g., an organic chemical composition) configured to bind and / or adhere to the sol-gel 102. The second layer 106 includes a paint, a primer, a topcoat, a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber reinforced composite material), a laminate, or a mixture thereof. The second layer 106 includes at least one of a polymer, a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a lacquer, a polyurethane, and a polyester. The second layer 106 may additionally include at least one of a pigment, a binder, a surfactant, a diluent, a solvent, a particle (e.g., a mineral filler), a corrosion inhibitor, and a fiber (e.g., carbon, aramid, and / or glass fiber).
[0106] The third layer 112 is disposed on a proximal surface 114 of the second layer 106 opposite the second surface 110 of the sol-gel 102. The third layer 112 includes an organic material (e.g., an organic chemical composition) configured to bind and / or adhere to the second layer 106. The third layer 112 includes a paint, a primer, a topcoat, a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber reinforced composite material), a laminate, or a mixture thereof. The third layer 112 includes at least one of a polymer, a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a paint, a polyurethane, and a polyester. The third layer 112 may additionally include at least one of a pigment, an adhesive, a surfactant, a diluent, a solvent, a particle (e.g., a mineral filler), a corrosion inhibitor, and a fiber (e.g., carbon, aramid, and / or glass fiber).
[0107] Sol-gel formation method
[0108] The method for forming the sol-gel of the present disclosure comprises mixing metal alkoxide, acetic acid and organic solvent, such as an anhydrous organic solvent, and then stirring for about 1 minute to about 1 hour, such as about 30 minutes. Then another organic solvent (for example, about 1vol% to 20vol% of organic solvent relative to the total volume, such as 5vol%) is added to the metal alkoxide / acetic acid mixture. Then the organosilane is added to the mixture and stirred for about 1 minute to about 1 hour, such as about 30 minutes. A corrosion inhibitor is added to the mixture in an amount of about 3wt% of the corrosion inhibitor relative to the mixture to about 15wt% of the corrosion inhibitor relative to the mixture. The mixture can be placed on a material substrate. The placed mixture can be cured at ambient temperature, or it can be heated to increase the rate of curing / sol-gel formation.
[0109] Figure 2 is a flow chart showing a method 200 of forming a sol-gel 102. Figure 2As shown, the sol-gel 102 can be formed by mixing 202 one or more sol-gel components. The sol-gel components include two or more of an organosilane, a metal alkoxide, an acid stabilizer, and a corrosion inhibitor, wherein the amount of the corrosion inhibitor is about 3 wt % of the corrosion inhibitor relative to the sol-gel to about 15 wt % of the corrosion inhibitor relative to the sol-gel. The mixed components are cured 208 to form the sol-gel 102.
[0110] Typically, mixing 202 is performed by dispersing (eg, emulsifying, suspending, and / or dissolving) the components of the sol-gel formulation in an organic solvent, preferably an anhydrous organic solvent, and optionally stirring the sol-gel formulation.
[0111] Mixing 202 includes mixing the sol-gel components to form a mixture (e.g., a solution, a mixture, an emulsion, a suspension, and / or a colloid). Mixing 202 includes mixing all of the sol-gel components simultaneously. Optionally, mixing 202 includes mixing any two components (e.g., a metal alkoxide and an acid stabilizer in an organic solvent) to form a first mixture, and then mixing the remaining components into the first mixture to form a second mixture. The first mixture and the second mixture each have a moisture content of about 0.1 wt % water relative to the mixture to about 10 wt % water relative to the mixture, such as from about 0.1 wt % to about 5 wt %, such as from about 0.1 wt % to about 3 wt %, such as from about 0.1 wt % to about 1 wt %, such as about 0.1 wt % to about 0.5 wt %, such as 0.5 wt % or less, such as 0.3 wt % or less, such as 0.1 wt % or less, such as 0 wt % or less, such as 0 wt %.
[0112] Mixing 202 may include dissolving, suspending, emulsifying, and / or dispersing the sol-gel components in an organic solvent prior to mixing with one or more other sol-gel components. Examples of solvents for dissolving, suspending, emulsifying, and / or dispersing the sol-gel components include one or more of alcohols (e.g., ethanol or propanol), ethylene glycol, propylene glycol, polyethylene glycol, polypropylene glycol, ethers (e.g., dimethyl ether or dipropylene glycol dimethyl ether), glycol ethers, tetrahydrofuran (THF), N-methyl-2-pyrrolidone (NMP), and dimethyl sulfoxide (DMSO).
[0113] Additionally or alternatively, mixing 202 can include mixing one or more solid, aggregate and / or powdered sol-gel components with one or more other sol-gel ingredients. For example, where mixing 202 includes mixing solids, powders and / or viscous liquids, mixing 202 can include mixing with a high shear mixer (e.g., a paint vibrator or a planetary centrifugal mixer or agitator). High shear mixers are useful for crushing and / or finely dispersing solids to form a substantially uniform mixture. For example, high shear mixers can dissolve, suspend, emulsify, disperse, homogenize, depolymerize and / or decompose solids into sol-gel formulations.
[0114] The sol-gel components during mixing 202 may be diluted to control the self-condensation reaction, thereby increasing the pot life of the mixed sol-gel formulation. Mixing 202 may include forming a weight percentage (wt%) by volume (metal alkoxide + organosilane + acid stabilizer relative to the mixture) in the mixture to be about 0.1 wt% to about 30 wt%, such as from about 0.3 wt% to about 20 wt%, such as from about 1 wt% to about 10 wt%, such as from about 1 wt% to about 5 wt%, such as from about 2 wt% to about 4 wt%, such as from about 2 wt% to about 3 wt%, for example, about 1 wt%, about 1.5 wt%, about 2 wt%, about 2.5 wt%, about 3 wt%.
[0115] Mixing 202 can include forming a weight percentage (wt %) of the corrosion inhibitor by volume in the mixture from about 0.1 wt % to about 50 wt %, such as from about 0.2 wt % to about 40 wt %, such as from about 0.5 wt % to about 35 wt %, such as from about 1 wt % to about 30 wt %, such as from about 2 wt % to about 25 wt %, such as from about 3 wt % to about 15 wt %, for example about 4 wt %, about 5 wt %, about 7 wt %, about 10 wt %, about 15 wt %. The sol-gel formulation contains a corrosion inhibitor, and mixing 202 includes forming the weight percentage (wt %) of the mixture (metal alkoxide + organosilane + acid stabilizer relative to the mixture) from about 0.3 wt % to about 50 wt %, such as from about 1 wt % to about 45 wt %, such as from about 2 wt % to about 40 wt %, such as from about 3 wt % to about 35 wt %, such as from about 4 wt % to about 25 wt %, such as from about 8 wt % to about 22 wt %, for example about 10 wt %, about 12 wt %, about 15 wt %.
[0116] During mixing 202, the volume ratio of organosilane to metal alkoxide in the sol-gel formulation is from about 5% to about 20%, for example, about 9% to about 11%, wherein the metal alkoxide has been pre-treated with an acid. For example, but not limited to, the volume ratio of organosilane to metal alkoxide is about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, etc. Higher ratios increase the % solids in the sol-gel coating and allow for mixing higher concentrations of inhibitor into the coating.
[0117] During mixing 202, the corrosion inhibitor can have a diameter of 90% of the total particles (D90) in the mixture that is less than a particle size of about 2 μm to about 5 μm, such as about 2 μm, about 3 μm, about 4 μm, or about 5 μm. Smaller particle sizes can allow the corrosion inhibitor to be uniformly mixed in the mixture. The particle size mentioned herein can refer to the average particle size. The average particle size can be determined in commercially classified products or determined by laser scattering according to various methods (e.g., ISO 4406).
[0118] The mixture of sol-gel components can be incubated 204 for a period of time, for example, from about 1 minute to about 60 minutes, such as from about 5 minutes to about 30 minutes, such as from about 10 minutes to about 20 minutes. In addition, the pot life is the time period from mixing to forming the sol-gel (for example, the mixture becomes too viscous to use). The pot life can be from about 1 hour to about 24 hours, such as from about 2 hours to about 8 hours, such as about 4 hours. Incubation 204 can be carried out under ambient conditions (for example, at room temperature) and / or at high temperature. Suitable incubation temperatures include about 10°C to about 100°C, such as from about 20°C to about 70°C, such as from about 30°C to about 50°C, for example, about 40°C.
[0119] Method 200 includes coating 206 a material substrate 104 with a mixture including a sol-gel component and incubating 204 the mixture. Incubating 204 includes allowing the mixture including the sol-gel component to stand at room temperature for about 30 minutes or more after mixing the mixture including the sol-gel component. Coating 206 may include wetting the material substrate 104 with the mixture including the sol-gel component, for example, by spraying, dipping, brushing and / or rubbing the mixture including the sol-gel component onto the material substrate 104. For example, suitable spraying forms include spraying with a spray gun, spraying with a high-volume low-pressure spray gun, and / or spraying with a hand pump sprayer. Allow the mixture including the sol-gel component to drain from the wet material substrate 104 for several minutes (e.g., 1-30 minutes, 1-10 minutes, or 3-10 minutes) and, if necessary, excess undried mixture may be sucked off the material substrate 104 and / or gently blown out of the material substrate 104 by compressed air.
[0120] Coating 206 includes cleaning and / or pre-treating the material substrate 104 before wetting the material substrate 104 with the mixture including the sol-gel component. Before applying the sol-gel coating, the metal substrate may be pre-treated by immersing it in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH. The solution may include about 3 g / L to 22 g / L of a water-soluble trivalent chromium salt, about 1.5 g / L to 11.5 g / L of an alkali metal hexafluorozirconate, about 0 g / L (e.g., 0.1 g / L) to 10 g / L of a water-soluble thickener, and about 0 g / L (e.g., 0.1 g / L) to 10 g / L of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and a combination thereof.
[0121] In general, the sol-gel 102 adheres and / or bonds well to a clean, bare material substrate that is substantially free of dirt, non-reactive surface oxides and / or corrosion products and preferably has a sufficient concentration of reactive hydroxyls or other chemically reactive species. The material substrate surface preparation method may include degreasing, alkaline washing, chemical etching, chemical deoxidation, mechanical deoxidation (e.g., sanding and / or grinding) and / or other suitable methods for producing a sol-gel compatible surface. Coating 206 generally does not include coating the metal substrate 104 with an undercoat or forming a chemical conversion coating on the metal substrate 104 unless the coating is applied to produce a hydroxyl-rich substrate or otherwise improved compatibility with the sol-gel. The material substrate surface can be made hydroxyl-rich by placing a hydroxy silicate on the material surface.
[0122] The method of the present disclosure includes solidifying a mixture including a sol-gel component. Figure 2 As shown, curing 208 may include drying a mixture including a sol-gel component placed on the material substrate 104 and may be performed under ambient conditions, at room temperature, and / or at elevated temperatures. The curing temperature is from about 10° C. to about 150° C., such as from about 30° C. to about 100° C., such as from about 50° C. to about 90° C., for example, about 60° C., about 70° C., about 80° C. Curing 308 may be performed for a period of time, such as from about 1 minute to about 48 hours, such as from about 5 minutes to about 24 hours, such as from about 10 minutes to about 8 hours, such as from about 30 minutes to about 4 hours, for example, about 1 hour.
[0123] After coating 206 and / or curing 208, the sol-gel is suitable for exposure to an external environment and / or application of a second layer 106. Figure 2As shown, placing 210 the organic material of the second layer 106 can be performed before the curing 208 is fully completed, for example, placing 210 the second layer 106 is performed at least partially simultaneously with the curing 208. Placing 210 can include painting, spraying, dipping, contacting, adhering and / or bonding the sol-gel 102 with the organic material to form the second layer 106. The second layer includes a primer, a coating, a fiber reinforced plastic, or other suitable organic material.
[0124] After coating 210, the sol-gel is suitable for exposure to apply the third layer 112. Placing 212 can include painting, spraying, dipping, contacting, adhering and / or bonding the second layer 106 with an organic material to form the third layer 112. The third layer includes paint, fiber reinforced plastic or other suitable organic material.
[0125] Example
[0126] Reference now Figure 3 , showing potentiodynamic scans of metal surfaces coated with sol-gel pretreatment. Comparative Example 3 is a bare metal surface. Comparative Example 2 is a sol-gel film of a coated metal panel with 3 vol.% composition. Comparative Example 1 is a sol-gel film of a coated metal panel with >3 vol.% composition. Inventive Example sol-gel is a sol-gel film of a coated metal panel with >3 vol.% composition + corrosion inhibitor.
[0127] As the vol.% of the components in the sol-gel increases, the coating weight / coating thickness increases, thereby increasing the passivation effect of the film on the metal surface. This increase in thickness leads to a decrease in corrosion current.
[0128] The inhibitor has cathodic inhibition properties, resulting in a shift in potential to negative values and a significant reduction in corrosion current.
[0129] Reference now Figure 4 , Experiment 1 corrosion inhibitor with 1,2,4DMcT provided the strongest corrosion inhibition compared to other organic or chromate inhibitors. The current value was monitored at -0.8V by potential current scan of the inhibitor dissolved in the electrolyte, where the metal surface served as the working electrode. The current at -0.8V indicated that a redox reaction occurred on the metal surface. The lower the ORR value, the greater the effect of the inhibitor, i.e., the inhibitor efficiency was improved.
[0130] Reference now Figure 5, showing the current-voltage graph of the electrode surface. The current for ORR on the metal surface is -0.8V. Without wishing to be bound by theory, it is assumed that the inhibition of the ORR current is due to the inhibitor action, i.e., the reaction of the inhibitor with the metal surface. Without wishing to be bound by theory, for thiol inhibitors, it is well known that the inhibitors bind to copper-rich sites on the surface of metal alloys. The corrosion inhibition of Inhibitors 1, 2, 3, and 4, which have about 3 wt % to about 15 wt % corrosion inhibitor, shows better inhibitor efficiency than the comparative example without corrosion inhibitor.
[0131] Reference now Fig. 6A and 6B The corrosion resistant sol-gel of the present disclosure can coat a metal substrate. The corrosion resistant sol-gel layer can be very thin, wherein the thin layer has fewer defects in the sol-gel, such as Fig. 6A The corrosion resistant sol-gel layer can be very thick, wherein the adhesion of the sol-gel to the material substrate, primer or topcoat can be improved, such as Figure 6B shown.
[0132] like Figure 7 As shown, the average thickness of the sol-gel of the present disclosure is between 100 nm and 4 μm. Figure 8 As shown, the average coating weight of the present invention is 40 mg / ft 2 Up to 400mg / ft 2 The increase in sol-gel coating weight improves barrier properties such as absorbance and passivation, e.g. Fig. 9 and Fig.10 shown.
[0133] Reference now Fig.11 , the electrical contact resistance increases with increasing coating thickness and weight. Three sample formulations of corrosion resistant sol-gels were prepared with increasing vol% of ingredients in the sol-gel and more inhibitors added to the film from formulation #1 to formulation #2 to formulation #3. The increase in vol% of sol-gel ingredients and inhibitors in the sol-gels resulted in an increase in coating weight and film thickness. Formulation #1 showed improved corrosion resistance in a salt spray chamber when compared to formulation #1. However, the surface contact resistance values also increased with increasing film thickness.
[0134] Reference now Fig.12, plots the impedance of the coated panel versus the frequency of the applied AC current. The fully chromated stack (chromate conversion coating (CCC) + chromate primer) has the highest impedance, while pretreatments without inhibitor + chromate primer or pretreatments with inhibitor + non-chromate primer have intermediate impedances, and finally pretreatments with CCC + non-chromate primer or no primer and non-chromate primer have the lowest impedance. Without wishing to be bound by theory, the addition of an inhibitor to the pretreatment increases the overall impedance of the film (i.e., improves corrosion resistance), thereby improving the performance of the non-chromate primer. As Figures 13A-13F As shown, corrosion is reduced when a material substrate is coated with the corrosion resistant sol-gel of the present disclosure compared to the comparative sol-gel.
[0135] like Figures 14A-14C As shown in Figure 2, the corrosion resistance of the chromate-free corrosion-resistant sol-gel of the present disclosure is comparable to that of the sol-gel coated with a chromate corrosion inhibitor. The corrosion resistance of the seashore specimens exposed outdoors for 9 months was monitored. Fig.14A The chromate treated stack shown is similar to the Fig. 14B and 14C The sol-gel pretreatment with a non-chromate primer stack for corrosion resistance shown was compared. All samples were found to have good corrosion resistance with no blistering in the field of view and no corrosion on the scribe line, as shown in Figure 2. Figures 14A-14C shown.
[0136] As shown in Table 1, no effect on paint adhesion was observed when the material substrate was coated with the corrosion resistant sol-gel of the present disclosure.
[0137] Table 1. Adhesion properties of sol-gel coated material substrates
[0138]
[0139] Preparation of corrosion-resistant sol-gel
[0140] The "A" solution was prepared by adding 22 mL of glacial acetic acid (GAA, Fischer Scientific) to 50 mL of zirconium propoxide (TPOZ, AcrosOrganics). Care was taken to ensure that all glassware was completely dry to avoid the formation of zirconium hydroxide. The resulting solution was clear and had a pale yellow color. The solution was allowed to stand for 10 minutes, and then 1000 mL of Milli-Q water was added to it. This A solution was used for all test matrices.
[0141] Then 10.8mL of glycidoxypropyltrimethoxysilane (GTMS, Acros Organics) was added to 108mL of Part A in a ThinkyTM planetary mixer container, mixed thoroughly and allowed to stand for 30 minutes. Then 0.6mL of a 10% volume aqueous solution of Antarox BL-204 (Solvay) was added, followed by the inhibitor. Then 2mm borosilicate glass beads were added to the Thinky cup to cover the bottom. The solution was then mixed in a ThinkyTM planetary mixer. (Step 1 - 500RPM 30s, Step 2 - 1000RPM 30s, Step 3 - 1500RPM 1min).
[0142] Inhibitor evaluation
[0143] Two inhibitors were obtained from AICLadvanced additives SZP-391JM and 430JM. Both inhibitors are jet milled materials with an average particle size of approximately 3 microns and a D99 of approximately 8 microns.
[0144] 1000 and 204 was obtained from WPC technologies. As described in the Results and Discussion section, More than 1000 versions were tested.
[0145] 2,5-Dimercapto-1,34-thiadiazole (DMCT) was obtained from Acros Organics; sodium benzoate and cerium nitrate were from Sigma-Aldrich. These compounds were used as received.
[0146] Panel pre-cleaning
[0147] All 7075-T6 panels were cleaned as follows: degreased in Brulin 815GD for 10 min, followed by alkaline cleaning in Bonderite C-AK for 12 min, and deoxidized in nitric acid / HF solution for 10 min.
[0148] The 7178-T6 panels were blasted with 180 grit brown fused aluminum oxide to remove any residual coating. The panels were then cleaned as described above for the 7075 panels.
[0149] Conversion coating and pretreatment applications
[0150] The various pretreatments and conversion coatings evaluated included SurTec 650V - SurTec's tri-chrome passivation, Alodine 5900 - Henkel's tri-chrome passivation, Alodine 1200S - Henkel's hexa-chrome conversion coating, and corrosion inhibitor sol-gels (-1 and -2).
[0151] SurTec coatings are applied using an immersion process. The solution is prepared using a 5% vol. aqueous solution of the concentrate. The pH of the solution is maintained between 3.7-3.95 using 1NH2SO4 or 1N NaOH. The cleaned panels are immersed in a SurTec 650V tank for 3 minutes, followed by two to three 15-30 second rinses in tap water and finally a 15 second rinse in deionized water. The panels are then dried using shop compressed air. The coating is transparent and translucent after drying.
[0152] The Alodine 5900 coating was brush-applied to the panels using the 5900 solution. To apply the coating by brushing, the cleaned panels were placed in a fume hood and the solution was brushed on, keeping the surface wet for 3 minutes. This was followed by two to three cycles of 15-30 second tap water rinses and 15 second deionized water rinses. The panels were then dried in an oven at 100-120°F for 1 hour. Once dry, the coating was blue in color.
[0153] The Alodine 1200S coating was brushed onto the panels. To apply the coating, the cleaned panels were placed in a fume hood and the solution was brushed on, keeping the surface wet for 3 minutes. This was followed by several cycles of 15-30 second tap water rinses and 15 second deionized water rinses. The panels were then dried in an oven at 100-120°F for 1 hour. The coating was golden in color after drying.
[0154] The corrosion resistant sol-gel of the present disclosure was formulated and applied using a conventional HVLP spray gun and then dried overnight at room temperature.
[0155] Application of primer and topcoat
[0156] All primers and topcoats were applied the day after the panels were pre-treated using the above pre-treatment. Both primers and topcoats were applied using conventional HVLP spray guns. Topcoats were applied within 4 hours of primer application and the coatings were cured at room temperature for 2 weeks. After a two-week drying period, the panels were scribed using a wide knife. Primer and topcoat thickness was measured using a witness coupon sprayed simultaneously with the panels. Primer and topcoat thickness was measured and recorded using a hand-held Elcometer thickness gauge.
[0157] Test Matrix
[0158] The test matrices described below evaluate several corrosion resistant sol-gel formulations in accordance with a new accelerated cyclic test method developed in accordance with ASTM B117 and BR&T4. BLIS18-00512 compares corrosion resistant sol-gel formulations to a control and a trivalent chromium pretreatment alternative. BLIS18-00614 evaluates the standalone corrosion resistance of lower wt% DMCT and Inhibicor 1000 in aqueous solution. BLIS18-00512-2 re-evaluates the sol-gel systems described herein in accordance with ASTM B117 exposure to 3000 hours.
[0159] Coating stripping
[0160] Coating and stripping
[0161] The coating was stripped from the test substrate BLIS18-00512-2 using a methylene chloride based stripper Bonderite Turco S-ST 5351. To strip the coating, the panels were immersed in the stripper overnight (some were immersed for about 6 hours). The efficiency of the stripper was recorded.
[0162] Inhibitor Screening in Corrosion Resistant Sol-Gels - Standalone Corrosion Protection
[0163] As shown in Table 2, several inhibitor chemistries were evaluated in the modified sol-gel formulations.
[0164] Table 2. Screening of independent protective inhibitors of 7075-T6 24-hour exposure to B117
[0165]
[0166] When 2 wt.% of corrosion inhibitor was added to the sol-gel for testing, The corrosion resistance of SZP-391JM sol-gel is better than 430JM corrosion resistant sol-gel. Addition of 1.24 wt.% loading of corrosion inhibitor to the sol-gel resulted in corrosion inhibition after 336 h of exposure to the NSS chamber. Some corrosion products resulting from inhibitor aggregation during drying are visible on the lower portion of the panel. The corrosion resistance of the sol-gel formulation was improved compared to that of the 1000 (larger particle size) formulation, in which the corrosion inhibitor content was 0.53 wt.%, and the sol-gel underwent extensive corrosion after exposure to the NSS chamber for 120 h.
[0167] The corrosion resistant sol-gel DMCT formulation is soluble in the modified sol-gel and when tested at 1.24 wt.% loading of corrosion inhibitor in the sol-gel, the independent corrosion resistance is improved compared to the sol-gel with 2.17 wt.% corrosion inhibitor. At 1.24 wt.% DMCT, there are no visible corrosion products after 336 h of independent corrosion testing.
[0168] Evaluation of aluminum-rich and lithium-rich primers in corrosion-resistant sol-gel formulations
[0169] Figures 15A-15F The coating of micronized unneutralized with aluminum (Al)-rich (Av-dec) and lithium (Li)-rich primers (Akzo Nobel Aerodur 2118) is shown. Results of the corrosion resistance sol-gel of 1000. After 2000h exposure in the NSS chamber, the panel coated with the aluminum-rich primer showed some blistering in the field of view, and white salt was present at the scribe line for both primers.
[0170] When coated with an aluminum-rich primer, the corrosion-resistant sol-gel containing DMCT also exhibited excellent corrosion performance after 2000 h of exposure in NSS. The scribe line darkened but without any corrosion products. When coated with a lithium-rich primer, the corrosion-resistant sol-gel containing DMCT exhibited poor corrosion resistance.
[0171] In a new accelerated salt spray corrosion test developed by Seattle Chem-Tech, BR&T, the The corrosion resistant sol-gel formulations of 1000 and DMCT were further tested.
[0172] 3000h ASTM B117 corrosion test using corrosion resistant sol-gel formulation
[0173] 7075-T6 bare panel
[0174] Alodine 1200S
[0175] Regardless of the pretreatment used, all 7075-T6 panels coated with primer RW-7171-64 showed poor corrosion resistance after 3000 h of NSS exposure, with white salt and corrosion on the scribe line and blistering in the field of view. Blistering on panel A-1-1-3 only appeared after 2000 h of exposure.
[0176] like Figures 16A-16DAs shown, the 7075-T6 panels coated with Alodine 1200S performed as well as Aerodur 2118 and PPG CA7231 after 3000h of exposure. The panels with Alodine 1200S and lithium-rich Aerodur 2118 had some blistering in the scribe. The scribes of all the panels coated with Alodine had many localized white salt spots in the scribe. After stripping the coating from panel A-1-(1-4)-3, no corrosion was visible on any of the panels in view, including under the small blisters on panel A-1-1-3. The Truco stripper had problems stripping the aluminum-rich primer, as seen from panel A-1-2-1, and the stripper did not remove the Alodine conversion coating from any of the panels. The stripper stripped the lithium-rich primer and both PPG primers.
[0177] Alodine 5900
[0178] like Figures 17A-17D As shown, the triple chrome pretreatment of Henkel Alodine 5900 with Aerodur 2118 lithium-rich primer has excellent performance. The 7075-T6 panel with Al-rich Av-Dec and PPG CA7231 exhibits blistering at the scribe line. Almost the entire surface of panel A-2-1-3 is covered with small blisters.
[0179] Dark staining of Al under the small blisters in the field of view can be seen in panel A-2-1-3. All large blisters on the scribe line show signs of pitting under the coating. Blisters appeared on panels A-2-1-3 and A-2-4-3 after 1000h of NSS exposure.
[0180] Turco stripper failed to strip the lithium-rich primer from panel A-2-3-(1-2), but was able to strip the PPG and Av-Dec primers.
[0181] SurTec 650V
[0182] Reference now Figures 18A-18D , SurTec 650V showed corrosion resistance and was compatible with Av-Dec, Aerodur 2118 and CA7231 primers. After 3000h exposure, none of these panels showed blistering in the field of view, but small blisters and pitting were observed on the scribe line below the coating in the case of Av-Dec and CA7231 primers. After 2000h exposure to NSS, the surface of panel A-3-1-3 was covered with small blisters, but there was no sign of corrosion under the blisters.
[0183] All blisters on panel A-3-(1-4)-3 occurred after 2000 h of NSS exposure. Except for Aerodur 2118, all other primers were stripped with Turco stripper.
[0184] Corrosion Resistant Sol-Gel
[0185] Reference now Figures 19A-19D , the corrosion resistant sol-gel pretreatment shows corrosion resistance when primed with Al-rich Av-Dec. Panels with corrosion resistant sol-gel as well as Aerodur 2118 and CA7231 have large blistering and white salt at the scribe line. Panel A-4-1-3 with RW7171-64 coating shows severe blistering in the field of view and at the scribe line.
[0186] After 1000 h of NSS exposure, blistering was visible on the scribe line of all panels pretreated with Sol-Gel-2, and this blistering and corrosion increased with exposure time. Turco Stripper did a poor job of stripping the primer from the panels pretreated with Sol-Gel-2. After stripping the primer from Panel A-4-(1-4)-3, it was clear that no corrosion was observed under the blister, but the blister near the scribe line had pitting under the paint.
[0187] 7178 Panel
[0188] Alodine 1200S
[0189] Panels with Alodine 1200S chromate corrosion inhibitor showed corrosion performance with RW-7171-64 primer and Aerodur 2118 primer. Figures 20A-20D As shown, the panel with Alodine 1200S and Av-Dec had some white salt at the score line, while the primer CA7231 had a few blisters along the score line under the primer and a lot of white salt at the score line.
[0190] None of the primers on Panel B-1-(1-4)-1 were stripped well using Truco Stripper. There was blistering on the score line with pitting underneath the paint.
[0191] Alodine 5900
[0192] Reference now Figures 21A-21C , Aerodur 2118 and RW7171-64 coated panels both had minimal salt in the scribe line and had creep. Panels coated with the Al-rich Av-Dec primer had salt in the scribe line and some blistering along the scribe line under the primer. When the coating was removed from these panels, pitting was visible along the scribe line below the blistering.
[0193] Truco stripper did not strip panel B-2-1-(1-2) primed with PPG RW-7171-64. After 1500 hours of exposure, the aluminum-rich primer was removed by the stripper, but after 3000 hours of exposure, the primer did not strip.
[0194] SurTec 650V
[0195] Reference now Figures 22A-22C , SurTec 650V with the Al-rich Av-Dec primer had minimal salt in the scribe and no blistering on the panels. The panels coated with Aerodur 2118 had salt in the scribe and RW7171-64 also had salt in the scribe and some blistering in the scribe. Pitting was clearly visible below the blistering in the scribe on these panels. The RW-7171-64 and Al-rich Av-Dec primers were not removed with Truco stripper.
[0196] Corrosion Resistant Sol-Gel-2
[0197] Reference now Fig.23A and 23B , the corrosion resistant sol-gel coated panel with Al-rich Av-Dec primer has small blisters. There is salt at the scribe line and some blisters at the scribe line. No corrosion is seen under the blisters in the field of view, while there is pitting of blisters adjacent to the scribe line under the primer of panel B-4-2-2.
[0198] The corrosion resistant sol-gel coated panel primed with RW 7171-64 showed ~1 / 16" blistering with white salt and blistering at the scribe. However, only the blistering at the scribe had pitting under the primer, and there was no corrosion under the primer at the blistering in view.
[0199] Truco Stripper did not strip the primer on these panels pretreated with Corrosion Resistant Sol-Gel-2.
[0200] Ranking of 7075-T6 and 7178Al panels after NSS corrosion testing
[0201] Reference now Fig.24 and 25 , the coated 7075-T6 and 7178Al panels after corrosion testing were ranked using Methods #1 and #2 described below.
[0202] Method #1 Ranking
[0203] Panels were numerically ranked based on their corrosion performance compared to the corrosion performance of other panels in a group.
[0204] Each panel was rated 1-15 based on scribe appearance, amount of white salt (corrosion product) in the scribe, blistering along the scribe, and blistering away from the scribe, as shown in Table 3. The scribe rating was based on creep measured in inches from the scribe, as shown in Table 4.
[0205] In groups containing the same pretreatment (and different primers), panels were numerically ranked from 1 to 2, 3, or 4, with 1 being the best candidate and 4 being the worst. The 7075-T6 Al panels were evaluated after 1000h, 2000h, and 3000h of exposure, and the 7178Al panels were evaluated after 1500h and 3000h of exposure.
[0206] SurTec 650V panels coated with Aerodur 2118, AvDec PT27703, AvDec-GK15-002E1, and PPG CA7231 exhibited corrosion resistance up to 9 months after application. The corrosion resistant sol-gel of the present disclosure coated with AvDec GK15-002E1 exhibited corrosion resistance up to 9 months after application.
[0207] Table 3. Corrosion level determination for method #1
[0208]
[0209] Table 4. Determination of the marking grade for method 1
[0210] Line level describe A No peristalsis B 0 to 1 / 64” C 1 / 64” to 1 / 32” D 1 / 32” to 1 / 16” E 1 / 16” to 1 / 8” F 1 / 8” to 3 / 16” G 3 / 16” to 1 / 4” H 1 / 4” to 3 / 8”
[0211] Method #2 Ranking
[0212] Each panel was assigned an independent score regardless of the performance of the other panels in the test matrix. The score / ranking for Method #2 was determined using 3 factors: 1) General Corrosion (GC) Rating; 2) Blister Size (BS) Rating; and 3) Blister Frequency (BF) Rating. Each 7075-T6 panel that completed 1000h, 2000h, and 3000h exposures was assigned a numerical value for each of the 3 criteria and the total score was calculated using equation (1) below.
[0213] The scores determined for each interval are weighted so that scores with longer exposure times are weighted more according to Equation 1 below. The 1000h score is multiplied by 0.2, the 2000h score is multiplied by 0.3, and the 3000h score is multiplied by 0.5. These weighted scores are then added together and the sum is divided by 2 to produce the final Method #2 score for each panel.
[0214] Method #2 Total score = ((((BS score 1000h *BF score 1000h ))+GC score 1000h )*0.2)+(((BS score 2000h *BF score 2000h )*0.3)+(((BS score 3000h *BF score 3000h )+GC score 3000h)*0.5))*0.5
[0215] Equation (1)
[0216] The general corrosion grade is determined based on the pitting observed around the scribe line and in the field of view on the debonded panel. The panel with the least corrosion is assigned the highest value of 10, while the panel with the most corrosion is assigned the lowest value of 2.
[0217] For blister size and frequency, a score was assigned based on the size and density of blisters observed in the field of view and on the scribe line of the coated panel. Panels with no blisters were assigned a blister frequency score of 1.
[0218] The weighting scheme for the composite score for the 7178-T6 panel was modified because there are only two intervals (at 1500 h and 3000 h) instead of three intervals (1000 h, 2000 h, and 3000 h) in the 7075-T6.
[0219] For the 7178-T6 panel, the score after 1500 hours of exposure is multiplied by 0.33, and the score after 3000 hours of exposure is multiplied by 0.67. As before, these two scores are added together and the sum is divided by 2 to obtain the final score.
[0220] The criteria for determining blister size and blister frequency for 7178 panels are the same as for 7075-T6 panels.
[0221] Comparison of corrosion resistance of coated 7075-T6 and 7178Al panels after NSS and cyclic accelerated corrosion tests
[0222] Method #2 scoring allows comparison of the corrosion performance of similar coating stacks between two different accelerated corrosion tests.
[0223] Reference now Fig.26 and 27 , it was observed that there was a huge difference in the performance of the stacks containing the corrosion resistant Sol-Gel-2 coating. The corrosion resistant Sol-Gel-2 / Al-rich Av-Dec coating was corrosion resistant under cyclic accelerated corrosion test conditions, but not in the ASTM B117 test.
[0224] Similar effects were observed for magnesium (Mg)-rich primers after ASTM B117 testing. It was observed that the magnesium-rich primers exhibited corrosion resistance in outdoor exposure and actual test conditions, but not in accelerated corrosion testing (per ASTM B117 conditions). A passive MgCO3 layer was formed upon outdoor exposure, which provided both anodic and cathodic corrosion protection. However, upon exposure to ASTM B117 conditions, a thin and porous Mg(OH)2 layer was formed, which exhibited lower corrosion resistance.
[0225] Other aspects
[0226] The present disclosure provides the following embodiments and the like, wherein each embodiment may be considered to optionally include any optional aspects thereof and combinations thereof.
[0227] Item 1. A coated substrate comprising: a metal substrate; a sol-gel coating disposed on the metal substrate, the sol-gel coating comprising a sol-gel comprising: a corrosion inhibitor, a surfactant, and a reaction product of an organosilane, a metal alkoxide, and an acid; and an organic primer coating disposed on the sol-gel coating, the organic primer coating having a plurality of metal particles.
[0228] Clause 2. The coated substrate according to Clause 1, wherein the corrosion inhibitor has two to three thiol moieties.
[0229] Item 3. The coated substrate according to Item 1 or 2, wherein the metal is selected from the group consisting of lithium, aluminum, magnesium, salts thereof, cations thereof, and combinations thereof.
[0230] Item 4. The coated substrate according to any one of items 1 to 3, wherein the metal is aluminum, a salt thereof, or a cation thereof.
[0231] Item 5. The coated substrate according to any one of items 1 to 4, wherein the metal is a combination of aluminum, a salt thereof or an aluminum cation, and magnesium, a salt thereof or a magnesium cation.
[0232] Clause 6. The coated substrate according to any one of clauses 1 to 5, wherein the organic primer is a polysiloxane or an epoxy resin.
[0233] Clause 7. The coated substrate according to any one of Clauses 1 to 6, wherein the epoxy resin is an amine cured epoxy resin.
[0234] Item 8. The coated substrate according to any one of Items 1 to 7, wherein the surfactant is ethylene oxide alcohol, propylene oxide alcohol or ethylene oxide propylene oxide alcohol.
[0235] Clause 9. The coated substrate according to any one of clauses 1 to 8, further comprising an organic topcoat disposed on the primer coating. Clause 10. The coated substrate according to any one of clauses 1 to 9, wherein the organic topcoat is a polyurethane.
[0236] Clause 11. The coated substrate of any of Clauses 1 to 10, wherein the thickness of the organic topcoat is from about 2 mils to about 3 mils, and the thickness of the organic primer coating is from about 0.3 mils to about 2.5 mils.
[0237] Clause 12. The coated substrate according to any one of clauses 1 to 11, wherein the organic corrosion inhibitor is a mercaptothiadiazole. Clause 13. The coated substrate according to any one of clauses 1 to 12, wherein the dimercaptothiadiazole is 2,5-dimercapto-1,3,4-thiadiazole.
[0238] Clause 14. The coated substrate according to any one of clauses 1 to 13, wherein the metal substrate is an aluminum substrate.
[0239] Clause 15. The coated substrate according to any one of Clauses 1 to 14, wherein the aluminum substrate is a 7075-T6 aluminum substrate or a 7178 aluminum substrate.
[0240] Item 16. The coated substrate according to any one of Items 1 to 15, wherein the sol-gel coating has a thickness of about 50 nm to about 4 microns.
[0241] Item 17. The coated substrate according to any one of Items 1 to 16, wherein the sol-gel coating has a thickness of about 100 nm to about 2.5 microns.
[0242] Clause 18. A coated substrate according to any one of clauses 1 to 17, wherein the weight of the sol-gel coating is about 30 mg / ft 2 About 400mg / ft 2 .
[0243] Clause 19. A coated substrate according to any one of clauses 1 to 18, wherein the weight of the sol-gel coating is about 250 mg / ft 2 About 1000mg / ft 2 , such as about 250mg / ft 2 About 350mg / ft 2 .
[0244] Item 20. The coated substrate according to any one of Items 1 to 19, wherein the average particle size of the metal particles of the plurality of metal particles is from about 1 micron to about 100 microns, such as from about 20 to about 30 microns, optionally from about 30 microns to about 40 microns.
[0245] Clause 21. The coated substrate of any one of Clauses 1 to 20, wherein the sol-gel coating has a corrosion inhibitor concentration of about 1 wt % to about 3 wt % by volume of the sol-gel coating.
[0246] Clause 22. The coated substrate of any one of Clauses 1 to 20, wherein the sol-gel coating has a corrosion inhibitor concentration of about 3 wt % to about 15 wt % by volume of the sol-gel coating.
[0247] Clause 23. The coated substrate of any one of Clauses 1 to 22, wherein the sol-gel coating has a corrosion inhibitor concentration of about 10 wt % to about 15 wt % by volume of the sol-gel coating.
[0248] Item 24. The coated substrate according to any one of Items 1 to 23, wherein the organosilane is glycidoxypropyltrimethoxysilane, the acid is acetic acid, and the metal alkoxide is zirconium propoxide.
[0249] Clause 25. A method of preparing a coated substrate, the method comprising: applying a sol-gel coating to a metal substrate to form a sol-gel coating, the sol-gel coating comprising a corrosion inhibitor; and applying a primer coating to the sol-gel coating to form a primer coating, the primer coating comprising a metal.
[0250] Clause 26. The method of Clause 25, wherein applying the sol-gel coating comprises mixing the corrosion inhibitor with an organosilane and a metal alkoxide, wherein the volume ratio of the organosilane to the metal alkoxide is from about 5% to about 20%, wherein the metal alkoxide has been pretreated with an acid.
[0251] Clause 27. The method according to clause 25 or 26, wherein the volume ratio of the organosilane to the metal alkoxide is from about 9% to about 11%. Clause 28. The method according to any one of clauses 25 to 27, wherein the metal of the primer coating is a metal particle independently selected from the group consisting of aluminum, lithium, magnesium, salts thereof, cations thereof, and combinations thereof.
[0252] Clause 29. The method of any one of Clauses 25 to 28, wherein the mixed corrosion inhibitor has a D90 particle size of about 2 microns to about 5 microns.
[0253] Clause 30. The method of any one of Clauses 25 to 29, further comprising pre-treating the metal substrate prior to applying the sol-gel coating to the metal substrate.
[0254] Clause 31. The method according to any one of Clauses 25 to 30, wherein the pretreatment comprises immersing the metal substrate in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH.
[0255] Clause 32. A method according to any one of clauses 25 to 31, wherein the solution comprises from about 3 grams to about 22 grams of a water-soluble trivalent chromium salt, from about 1.5 grams to about 11.5 grams of an alkali metal hexafluorozirconate, from about 0 grams to about 10 grams of a water-soluble thickener, and from about 0 grams to about 10 grams of a water-soluble surfactant selected from the group consisting of nonionic surfactants, anionic surfactants, and cationic surfactants, and combinations thereof, per liter of solution.
[0256] Item 33. A coated substrate comprising: a metal substrate; a sol-gel coating disposed on the metal substrate, the sol-gel coating comprising a sol-gel, the sol-gel comprising: a corrosion inhibitor, a surfactant, and a reaction product of an organosilane, a metal alkoxide, and an acid; and an organic primer coating comprising an organic primer and disposed on the sol-gel coating, the organic primer coating having a plurality of metal particles.
[0257] Item 34. The coated substrate according to Item 33, wherein the corrosion inhibitor has two or more thiol moieties.
[0258] Item 35. The coated substrate according to Item 33 or 34, wherein the metal is selected from the group consisting of lithium, aluminum, magnesium, salts thereof, cations thereof, and combinations thereof, wherein the metal is optionally aluminum, a salt thereof, or a cation thereof.
[0259] Item 36. The coated substrate according to any one of Items 33 to 35, wherein the organic primer is a polysiloxane or an epoxy resin, wherein the epoxy resin is optionally an amine-cured epoxy resin.
[0260] Clause 37. A coated substrate according to any one of clauses 33 to 36, wherein the surfactant is ethylene oxide alcohol, propylene oxide alcohol or ethylene oxide propylene oxide alcohol.
[0261] Clause 38. The coated substrate according to any one of Clauses 33 to 37, wherein the corrosion inhibitor is a mercaptothiadiazole, wherein the dimercaptothiadiazine is optionally 2,5-dimercapto-1,3,4-thiadiazole.
[0262] Clause 39. The coated substrate of any one of Clauses 33 to 38, wherein the sol-gel coating has a corrosion inhibitor concentration of about 1 wt % to about 15 wt % by volume of the sol-gel coating.
[0263] Item 40. The coated substrate according to any one of Items 33 to 39, wherein the organosilane is glycidoxypropyltrimethoxysilane, the acid is acetic acid, and the metal alkoxide is zirconium propoxide.
[0264] Clause 41. A method of preparing a coated substrate, the method comprising: applying a sol-gel coating to a metal substrate to form a sol-gel coating, the sol-gel coating comprising a corrosion inhibitor, and applying a primer coating to the sol-gel coating to form a primer coating, the primer coating comprising a metal.
[0265] Item 42. The coated substrate of Item 41, wherein applying the sol-gel coating comprises mixing a corrosion inhibitor with an organosilane and a metal alkoxide.
[0266] Item 43. A coated substrate according to Item 41 or 42, wherein the volume ratio of the organosilane to the metal alkoxide is from about 5% to about 20%, wherein the metal alkoxide has been pretreated with an acid and / or wherein the volume ratio of the organosilane to the metal alkoxide is from about 9% to about 11%.
[0267] Clause 44. The method of any one of clauses 41 to 43, wherein the metal of the primer coating is a plurality of metal particles independently selected from the group consisting of aluminum, lithium, magnesium, salts thereof, cations thereof, and combinations thereof, wherein the mixed corrosion inhibitor optionally has a D90 particle size of about 2 microns to about 5 microns.
[0268] Clause 45. The method of any one of Clauses 41 to 44, further comprising pre-treating the metal substrate before applying the sol-gel coating to the metal substrate.
[0269] Clause 46. The method of Clause 45, wherein the pretreatment comprises immersing the metal substrate in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH.
[0270] Clause 47. A method according to Clause 46, wherein the solution comprises from about 3 grams to about 22 grams of a water-soluble trivalent chromium salt, from about 1.5 grams to about 11.5 grams of an alkali metal hexafluorozirconate, from about 0 grams to about 10 grams of a water-soluble thickener, and from about 0 grams to about 10 grams of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and combinations thereof, per liter of solution.
[0271] Although we have described preferred aspects, those skilled in the art will readily recognize that substitutions, changes and modifications may be made without departing from the inventive concept. Therefore, based on this specification, the claims are to be interpreted literally with the support of the full range of equivalents known to those of ordinary skill in the art. These examples illustrate the disclosure but are not intended to limit it. Therefore, the claims are used to define the disclosure and to limit the claims only when necessary, based on the relevant prior art.
Claims
1. A coated substrate comprising: Metal substrate; A sol-gel coating disposed on the metal substrate, the sol-gel coating comprising a sol-gel, the sol-gel comprising: Corrosion inhibitors, Surfactants, and Reaction products of organosilanes, metal alkoxides and acids; and An organic primer coating includes an organic primer and is disposed on the sol-gel coating, wherein the organic primer coating has a plurality of metal particles.
2. The coated substrate of claim 1, wherein the corrosion inhibitor has two or more thiol moieties.
3. The coated substrate according to claim 1 or 2, wherein the metal is selected from the group consisting of lithium, aluminum, magnesium, salts thereof, cations thereof, and combinations thereof, wherein the metal is optionally aluminum, a salt thereof, or a cation thereof.
4. A coated substrate according to any one of claims 1 to 3, wherein the organic primer is a polysiloxane or an epoxy resin, wherein the epoxy resin is optionally an amine-cured epoxy resin.
5. A coated substrate according to any one of claims 1 to 4, wherein the surfactant is ethylene oxide alcohol, propylene oxide alcohol or ethylene oxide propylene oxide alcohol.
6. The coated substrate according to any one of claims 2 to 5, wherein the corrosion inhibitor is a mercaptothiadiazole, wherein the dimercaptothiadiazole is optionally 2,5-dimercapto-1,3,4-thiadiazole.
7. The coated substrate of any one of claims 1 to 6, wherein the concentration of the corrosion inhibitor of the sol-gel coating is from about 1 wt% to about 15 wt% by volume of the sol-gel coating.
8. The coated substrate of any one of claims 1 to 7, wherein the organosilane is glycidoxypropyltrimethoxysilane, the acid is acetic acid, and the metal alkoxide is zirconium propoxide.
9. A method for preparing a coated substrate, the method comprising: applying a sol-gel coating to a metal substrate to form the sol-gel coating, the sol-gel coating comprising a corrosion inhibitor; and A primer coating is applied to the sol-gel coating to form the primer coating, the primer coating comprising a metal.
10. The method of claim 9, wherein applying the sol-gel coating comprises mixing the corrosion inhibitor with an organosilane and a metal alkoxide.
11. The method of claim 9 or 10, wherein the volume ratio of organosilane to metal alkoxide is from about 5% to about 20%, wherein the metal alkoxide has been pretreated with an acid and / or wherein the volume ratio of organosilane to metal alkoxide is from about 9% to about 11%.
12. The method of any one of claims 9 to 11, wherein the metal of the primer coating is a plurality of metal particles independently selected from the group consisting of aluminum, lithium, magnesium, salts thereof, cations thereof, and combinations thereof, wherein the corrosion inhibitor after mixing optionally has a D90 particle size of about 2 microns to about 5 microns.
13. The method of any one of claims 9 to 12, further comprising pre-treating the metal substrate before applying the sol-gel coating to the metal substrate.
14. The method of claim 13, wherein the pretreatment comprises immersing the metal substrate in a solution having a pH value maintained between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH.
15. The method of claim 14, wherein the solution comprises from about 3 grams to about 22 grams of a water-soluble trivalent chromium salt, from about 1.5 grams to about 11.5 grams of an alkali metal hexafluorozirconate, from about 0 grams to about 10 grams of a water-soluble thickener, and from about 0 grams to about 10 grams of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, and a cationic surfactant, and combinations thereof, per liter of solution.